A prática de exercício físico e/ ou atividade física: percepção das pessoas idosas - Gonçalves, Vanusa Antonio (Universidade Federal do Tocantins, 2024)
The practice of physical exercise and/or physical activity can promote numerous benefits for those who practice them. For the elderly population, staying active can minimize the deleterious effects of aging. The research presented here aimed to identify whether the elderly participants perceive the importance of physical exercise or physical activity. Methodologically, the research is a cross-sectional, non-probabilistic, descriptive and quantitative study. Participants were 14 elderly people who were divided into two groups: Physical Exercise Practitioners (PEF) and Non-Physical Exercise Practitioners (NPEF). For data collection, we opted for a structured interview and the application of the International Physical Activity Questionnaire – IPAQ. The descriptive data were. Descriptive data were presented as percentages, median (Md) and interquartile range (IQR). For unpaired samples, the Mann-Whitney test was used (intergroup analysis). All analyses were performed using the Statistical Package for the Social Sciences - SPSS® version 20.0 for Windows®. The level of significance adopted in the present study was p <0.05. Through the results presented and although there is some confusion on the part of some participants about the concept of the terms "Physical Exercise" and "Physical Activity", all participants (100%) expressed the importance of the practice of physical exercise.